2004
DOI: 10.1063/1.1807023
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high electron mobility of pseudomorphic In0.74Ga0.26As∕In0.46Al0.54As modulation-doped quantum wells grown on (411)A InP substrates by molecular-beam epitaxy

Abstract: Universal behavior of photoluminescence in GaN-based quantum wells under hydrostatic pressure governed by built-in electric field J. Appl. Phys. 112, 053509 (2012) Effects of scattering on two-dimensional electron gases in InGaAs/InAlAs quantum wells J. Appl. Phys. 112, 023713 (2012) Superlinear electroluminescence due to impact ionization in GaSb-based heterostructures with deep Al(As)Sb/InAsSb/Al(As)Sb quantum wells J. Appl. Phys. 112, 023108 (2012) Study of nitrogen incorporation into GaInNAs: The role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We have reported that extremely flat heterointerfaces can be realized in QWs grown on (411)A-oriented substrates by molecular beam epitaxy (MBE), not only for GaAs/AlGaAs system [2,3] but also for InGaAs/InAlAs system [4,5]. We also reported that pseudomorphic (411)A In 0.74 Ga 0.26 As/In 0.52 Al 0.48 As MD-QW shows electron mobility of as high as 105,000 cm 2 /Vs with a sheet electron concentration (N s ) of 3.1 × 10 12 cm -2 at 77 K [6]. Recently, wavenumber dependence of the Fourier components of the interface roughness was deduced by analyzing N s dependence of electron mobility (15 K) of pseudomorphic In 0.74 Ga 0.26 As/In 0.52 Al 0.48 As MD-QWs, and height and lateral size of the roughness in the (411)A and (100) interfaces were characterized [7].…”
mentioning
confidence: 75%
“…We have reported that extremely flat heterointerfaces can be realized in QWs grown on (411)A-oriented substrates by molecular beam epitaxy (MBE), not only for GaAs/AlGaAs system [2,3] but also for InGaAs/InAlAs system [4,5]. We also reported that pseudomorphic (411)A In 0.74 Ga 0.26 As/In 0.52 Al 0.48 As MD-QW shows electron mobility of as high as 105,000 cm 2 /Vs with a sheet electron concentration (N s ) of 3.1 × 10 12 cm -2 at 77 K [6]. Recently, wavenumber dependence of the Fourier components of the interface roughness was deduced by analyzing N s dependence of electron mobility (15 K) of pseudomorphic In 0.74 Ga 0.26 As/In 0.52 Al 0.48 As MD-QWs, and height and lateral size of the roughness in the (411)A and (100) interfaces were characterized [7].…”
mentioning
confidence: 75%
“…The (411)A orientation is known to allow higher electron mobility and narrower photoluminescence in quantum wells (QWs). [24][25][26] Our own results on InGaAs/InAlAs double-QW structures lattice-matched to InP have confirmed a marked increase in the electron mobility in (411)A oriented samples 27 and have inspired us to investigate if a reduced intrasubband scattering seen in transport translates into a reduction in intersubband scattering that is detrimental to QCL operation. In this letter, we compare the intersubband scattering due to IFR scattering in lattice-matched QCLs grown on (411)A to (100) InP substrates.…”
mentioning
confidence: 89%